Using Mentimeter in Action Research to Enhance Students' Engagement in Online Learning (JEELL (Journal of English Education, Linguistics and Literature), 2025)
In online learning, improving student participation in EFL classes is still a growing concern. Fortunately, several studies have demonstrated a favorable relationship between using technology to increase student engagement. This action research study investigated the effect of using a mentimeter on the student’s engagement in online learning. The study used a classroom cyclic action-research approach to enhance student engagement over a month. The participants were 22 second-year-undergraduate students from the local university in Indonesia, consisting of 7 males and 15 females. Findings revealed that engaging students in engaged discussion enhances their engagement and achievement in the word cloud and open-ended questions model using a mentimeter. The students gave positive responses after being taught by using a mentimeter. The findings support the enhancement of the students’ engagement in English as a Foreign Language (EFL) learning context and suggest useful implications for educators.